2016
DOI: 10.3892/or.2016.5017
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TRIB3 promotes angiogenesis in human gastric cancer

Abstract: Tribbles homolog 3 (TRIB3) plays important roles in many types of malignancies. However, whether TRIB3 is involved in the development or progression of gastric cancer (GC) remains unclear. In this study, we analyzed TRIB3 expression in GC tissues from 191 GC patients categorized with stage I to Ⅳ disease, to examine the role of TRIB3 in GC, and examined the relationship between TRIB3 and tumor angiogenesis. We found that TRIB3 expression was significantly higher in GC tissues than that in adjacent non-tumor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
(36 reference statements)
2
20
0
Order By: Relevance
“…NRP1 is also expected to be a therapeutic target for gastric cancer; the study of Zhang et al showed that the new tumor homing peptide iRGD could enhance the 5-FU chemotherapy effect on gastric cancer through NRP1 [ 28 ]. Dong et al believed that the overexpression of TRIB3 was related to tumor angiogenesis and poor prognosis in gastric cancer patients and TRIB3 was a promising molecular target for antiangiogenic therapy in gastric cancer [ 29 ]. Moreover, Wu et al proposed that the expression of TRIB3 could affect the apoptosis induced by the anticancer drug adriamycin, indicating that TRIB3 expression in response of anticancer drugs may reflect the therapeutic efficacy of gastric cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…NRP1 is also expected to be a therapeutic target for gastric cancer; the study of Zhang et al showed that the new tumor homing peptide iRGD could enhance the 5-FU chemotherapy effect on gastric cancer through NRP1 [ 28 ]. Dong et al believed that the overexpression of TRIB3 was related to tumor angiogenesis and poor prognosis in gastric cancer patients and TRIB3 was a promising molecular target for antiangiogenic therapy in gastric cancer [ 29 ]. Moreover, Wu et al proposed that the expression of TRIB3 could affect the apoptosis induced by the anticancer drug adriamycin, indicating that TRIB3 expression in response of anticancer drugs may reflect the therapeutic efficacy of gastric cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of evidence has demonstrated that a wide variety of molecules such as miRNAs and genes are probably associated with EC 2325. Remarkably, TRIB3 has recently been reported to be implicated in multiple cancers including tongue squamous cell carcinoma, gastric cancer, and breast cancer 18,26,27. In the present study, the findings revealed that TRIB3 expression levels were enhanced in endometrioid adenocarcinoma compared with the normal tissues, and TRIB3 could promote apoptosis and inhibit proliferation and colony formation of EC cells and possibly plays important roles in the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of HMGA2 has been seen in breast, ovarian and colon cancer and pancreatic adenocarcinoma [2225]. Overexpression of TRIB3 is associated with tumor angiogenesis and a poor prognosis in patients with gastric cancer [26], and patients with high TRIB3 expression were susceptible to a recurrence of the disease, and showed poorer overall survival than those with low expression [27].…”
Section: Discussionmentioning
confidence: 99%